Sistem Informasi Penjualan Undangan Pernikahan Online Berbasis Web Di Kota Palangka Raya - Sari, Nova Noor Kamala; Diantoro, Ironaldo (Universitas Palangka Raya, 2022)
Sales of wedding invitations have been experiencing various problems in the marketing process from consumer to consumer. In addition, product sales still use a catalog sales system in the form of books and compete fiercely with other printing houses near the location. Another problem is the distance and time that make it difficult for customers to get invitation booking information at the printing house. Therefore, this study aims to make it easier for customers to order and sell invitations online through a wedding invitation sales website in Palangka Raya City. The research methods carried out include data collection methods with two stages, namely literature studies and literature studies, as well as software development using the Waterfall (Pressman) method. System and software design is done using Chris Gane and Trish Sarson's DFD (Data Flow Diagram), ERD (Entity Relationship Diagram), and interface design using Story Board. Program creation using PHP and JavaScript programming languages, CI framework (CodeIgniter), Visual Studio Code, and MySQL database. The results showed that the Web Print Invitation has been made in accordance with the design design and testing stages of the program using BlackBox Testing. Testing of the system has been successfully carried out so that functionally the website can run quite well and according to needs, and produce the expected output.